2022
DOI: 10.3390/nano12162860
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Magneto-Plasmonic Nanoparticles for SERS with Tunable Plasmon Resonance

Abstract: Bifunctional magneto-plasmonic nanoparticles that exhibit synergistically magnetic and plasmonic properties are advanced substrates for surface-enhanced Raman spectroscopy (SERS) because of their excellent controllability and improved detection potentiality. In this study, composite magneto-plasmonic nanoparticles (Fe3O4@AgNPs) were formed by mixing colloid solutions of 50 nm-sized magnetite nanoparticles with 13 nm-sized silver nanoparticles. After drying of the layer of composite Fe3O4@AgNPs under a strong m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…This interaction was described in our previous and other research works. 38,39 Meanwhile, the increase in the concentration of gold nanoparticles resulted in higher intensity of absorption for two visible plasmonic peaks at 550 nm and 720 nm. The explanation for the appearance of these two peaks is the same as for the AgNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interaction was described in our previous and other research works. 38,39 Meanwhile, the increase in the concentration of gold nanoparticles resulted in higher intensity of absorption for two visible plasmonic peaks at 550 nm and 720 nm. The explanation for the appearance of these two peaks is the same as for the AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that the magnetic properties of nanoparticles contribute to a higher enhancement factor and narrower distribution of SERS intensities within a single sample and among the samples from different batches. 39 Fig. 8 demonstrates SERS spectra from 4-MBA modified nanoparticles of different compositions.…”
Section: Multiwavelength Raman Characterization Of Composite Nanopart...mentioning
confidence: 99%
“…The wet chemical synthesis approach, outlined in our earlier work, generates magnetite cubes averaging around 50 nm in diameter. 9 The TEM image in Figure 3B demonstrates a uniform magnetite distribution. Conversely, pulsed laser ablation in liquid results in plasmonic nanoparticles of a higher average size with a broader distribution.…”
Section: Characterization Of Hybrid Magneto-plasmonic Nanoparticles C...mentioning
confidence: 95%
“…Then, 2.5 mL of 2 M KNO 3 (Reachem, Bratislava, Slovakia), 2.5 mL of 1 M NaOH (Carl Roth GmbH, Karlsruhe, Germany), and 5 mL of 8 mg/mL PEI (M w = 2500; Sigma-Aldrich, Steinheim, Germany) were added and magnetically stirred under a N 2 gas flow at 90 °C for 2 h. After the solution cooled, the magnetic nanoparticles were triple-washed with deionized water and decorated with either silver, gold, or silver−gold alloy nanoparticles according to the procedure described elsewhere. 9 To obtain hybrid nanoparticles (MPNPs), 10 mL of the plasmonic nanoparticles was mixed with 0.8 mL of the Fe 3 O 4 colloidal solution. After a 45 min ultrasound treatment, the decorated nanoparticles (termed Fe 3 O 4 @Ag, Fe 3 O 4 @Au, Fe 3 O 4 @Ag 80 Au 20 , and Fe 3 O 4 @Ag 50 Au 50 ) were collected by using a strong magnet and washed with distilled water three times.…”
Section: Synthesis Of Plasmonic and Magneto-plasmonicmentioning
confidence: 99%
“…For the selection and separation of biological and chemical molecules, the most commonly used method is Surface-Enhanced Raman Spectroscopy (SERS). As evidenced by several studies [ 75 , 76 , 77 , 78 ], the use of plasmonic nanoparticles, in particular Au NPs for their high chemical stability and their SPR support in the visible region, can significantly improve the SERS signal both in vitro and in vivo.…”
Section: Main Applications Of Magneto-plasmonic Heterostructures In T...mentioning
confidence: 99%